Test on wear of roll bearings in the heavy modes of exploitation 1. Methods and equipments - Гайдамака, А.В. (Problems of Tribology, 2014)
In work, according to the basic types of damages of roll bearings of the wheeled pairs of carriages and locomotives with the purpose of rise of their wearproof, the methods of the forced tests are offered on tearing down of working surfaces of details and equipment for realization of methods. Advantages of new methods of test are shown, possibility of their application for any roll bearings of the heavy modes of exploitation, that the insufficient wearproof is had.